The effects of local and systemic inflammatory status on iron metabolism and lipid profile in calves - Uğur Aydoğdu; İbrahim Yurdakul (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to determine the effects of local and systemic inflammatory status on iron metabolism and lipid profile in calves. Materials and Methods: A total of 56 calves, 39 sick and 17 healthy, were used in the study in different races and genders. The sick calves were divided into two groups as local (8 omphalitis and 11 arthritis) and systemic (10 enteritis and 10 pneumonia) inflammations. After routine clinical examinations of all the animals were performed, 8 ml of blood was taken for blood analysis and biochemical analyses were performed. Results: Serum iron, total cholesterol (TC), high density lipoprotein (HDL) and albumin levels were significantly (p <0.05) lower in calves with local and systemic inflammation compared to the control group. Serum urea and creatinine levels were significantly (p <0.05) higher in calves with systemic inflammation compared to the control group. Conclusion: As a result, it was evaluated that low iron, total cholesterol, HDL and albumin levels may indicate to local and systemic inflammation in calves.